2019
DOI: 10.1097/sla.0000000000003192
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection for Multiple Hepatocellular Carcinomas

Abstract: Objective: The aim of the study was to evaluate the survival benefits of liver resection (LR) compared with transarterial chemoembolization (TACE) for patients with multiple hepatocellular carcinomas (HCCs). Background: Despite significant improvements in diagnostic imaging and the widespread application of screening programs, some patients with HCC continue to present with multiple tumors. The surgical indications for multiple HCCs remain controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 37 publications
1
52
1
Order By: Relevance
“…154,155 In addition, a large observational study focusing only on multinodular tumours (up to 3 lesions) confirmed better 5-year OS after LR compared to TACE (60% vs. 41.6%, p <0.001) and even for tumours >3 cm. 156 LR may yield better long-term survival than TACE for patients with BCLC-B HCC, but the identification of good candidates is crucial in order to avoid high rates of perioperative morbidity.…”
Section: Overcoming Old Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…154,155 In addition, a large observational study focusing only on multinodular tumours (up to 3 lesions) confirmed better 5-year OS after LR compared to TACE (60% vs. 41.6%, p <0.001) and even for tumours >3 cm. 156 LR may yield better long-term survival than TACE for patients with BCLC-B HCC, but the identification of good candidates is crucial in order to avoid high rates of perioperative morbidity.…”
Section: Overcoming Old Barriersmentioning
confidence: 99%
“… Study Characteristics of the study Characteristics of the patients and surgical procedures Outcomes and morbi/mortality LR TACE p value LR TACE p value Fukami et al. Ann Surg 2019 156 Japan 2000–2007; Observational retrospective Study; Propensity matching 1 Patients HBV Cirrhosis Portal hypertension 3 tumours HCC Tumour size ≥3 cm Vascular invasion 1,944 22% 26% 67% 13% 1,302 12% 36% 57% 7% <0.001 <0.001 <0.001 <0.001 Global 5-year OS With propensity score 1 Complications (Grade 3–4) Hospital mortality 52% 60% n.d. 0.57% 42% 41.6% n.d. 0% <0.001 <0.001 n.d. n.s. Yin et al.…”
Section: Overcoming Old Barriersmentioning
confidence: 99%
“…On multivariate analysis, the survival of patients with synchronous multiple HCC was shorter in the older patients with larger tumors, tumor thrombus, and liver cirrhosis. Given that surgical outcomes of patients with multiple HCC are not preferable (9,10), the candidates for liver resection should be determined based on the patient background, tumor status, and liver function (20); however, studies have showed the superiority of liver resection to TACE for multiple HCC (6,7).…”
Section: Figure 2 Survival Of Patients With Multiple Hcc (A)mentioning
confidence: 99%
“…Multiplicity is one of the characteristics of hepatocellular carcinoma (HCC) (1), and patients with multiple HCC, classified as the intermediate stage (B) in the Barcelona-Clinic Liver Cancer staging classification, are candidates for transcatheter arterial chemoembolization (TACE) (2). In contrast, the survival benefit of liver resection for multiple HCC has been reported (3)(4)(5); survival of patients undergoing liver resection for such nodules was longer than that of patients undergoing TACE according to a nationwide study (6) and a prospective study (7). Consequently, resection of multiple HCC ≤ 3 is indicated by clinical practice guidelines for hepatocellular carcinoma in Japan (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although improvements in many therapeutic strategies, including surgical resection, liver transplantation, and radiofrequency ablation, have improved the 5-year survival rate of HCC patients, its prognosis remains unsatisfactory [2]. Survival is associated with the use of targeted treatments, such as the tyrosine kinase inhibitor sorafenib, in patients with advanced stage cancer with vascular invasion and distant metastasis [3,4].…”
Section: Introductionmentioning
confidence: 99%